Characteristics of oxide films on TA16 alloy after long-term exposure in simulated secondary circuit water environment of small modular reactor - Yuxiang Zhao; Hao Wang; Shuangshuang Zhong; Linjiang Chai; Qi Xu; Tao Zhou (Journal of Materials Research and Technology)
Currently, little is known about the characteristics of oxide films on Ti alloys exposed to the secondary circuit water environment of small modular reactors (SMRs). In this study, multiple microstructural characterization techniques were employed to meticulously characterize the oxide film characteristics of the TA16 alloy after 6000 h and 8000 h of exposure to a simulated SMR secondary circuit water environment. The results indicate that the oxide films on the 6000 h specimen are composed of a microcrystalline anatase TiO2 interior layer and a coarse-grained anatase TiO2 exterior layer, while the oxide film on the 8000 h specimen typically consists of a microcrystalline anatase TiO2 inner layer, an NiFe2O4 middle layer, and a coarse-grained anatase TiO2 outer layer. As the corrosion time is extended to 8000 h, the presence of NiFe2O4 oxide particles can be attributed to oxide deposition by the 316L stainless steel autoclave used in the corrosion experiments, which results in the migration of Ni and Fe ions onto the surface of the Ti alloy.